OCEANIC ANOXIA AT THE PRECAMBRIAN-CAMBRIAN BOUNDARY - Kimura H.; Watanabe Y. (My University, 2001)
The Precambrian-Cambrian (PC-C) boundary separates fossils representing two discrete evolutionary phases: the Neoproterozoic soft-bodied Ediacarian biotas and Cambrian small shelly faunas. The biological discontinuity is suspected to have been a result of mass extinction; however, recent discoveries of the Ediacarian biotas in Cambrian sediments have led to an understanding that the faunal change was gradual through the PC-C transition. Th/U ratios, which are high in oxidizing conditions and low in reducing conditions, show a considerable positive correlation with delta13C values at all studied sites of the PC-C boundary. This correlation indicates that reported delta13C variation across the PC-C boundary from numerous localities corresponds to redox variation in the depositional environment. The negative delta13C anomaly that occurs worldwide at the PC-C boundary, therefore, corresponds to the widespread development of an oxygen-deficient shallow marine environment. This finding suggests that widespread oceanic oxygen deficiency, which has been interpreted to reflect Phanerozoic mass extinction events, also occurred immediately before the Cambrian explosion.
Keywords: anoxic environments; bioturbation; mass extinctions; Cambrian; Precambrian; Paleozoic::Cambrian; Precambrian; Палеозой::Кембрийская; Докембрий